High Dynamic Range Structured Illumination Microscope Based on Multiple Exposures - Liang, Yong; Chen, Xiaohu; Sun, Zhenglong; Wen, Gang; Chen, Chong; Wang, Libo; Jin, Xin; Zhang, Jie; Yang, Guang; Gao, Jing; Li, Hui; Li, Simin (Frontiers in Physics, 2021)
Structured illumination microscope (SIM) can double the spatial resolution by using fringed pattern illumination. However, for samples with large intra-scene dynamic ranges, such as clustered objects, SIM fails to reconstruct high-quality images and often exhibits strong artifacts. Herein, we present a high dynamic range SIM (HDR-SIM) method using a multi-exposure acquisition strategy. With HDR-SIM, individual and clustered microspheres and vesicles with 420 times intensity differences can be visualized in the same scene while the delicate structure of sample was preserved effectively.